2019
DOI: 10.18203/2394-6040.ijcmph20190211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated to depression among geriatric population in a rural area of Kanyakumari district Tamil Nadu

Abstract: Background: Aging is a universal process. It has been documented that elderly are more prone to psychological problems and depression is the commonest geriatric psychiatric disorder. In India the prevalence of depression among elderly population between 13% and 25%. Depression usually becomes unnoticed and untreated in the elderly. Depression in late life is associated with significant morbidity including deficits in a range of cognitive functions, functional impairment, decreased quality of life, increased ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Contextual characteristics such as family support, good communication among family members, and family decision-making roles were also associated to depression. However, sex and individual factors such as cigarette use, alcohol consumption, and the presence of chronic disease were not associated to geriatric depression, which is consistent with earlier findings; a study conducted by Shrestha, Shrestha [6] found an association between the presence of chronic disease and depression and no association between age and depression, John and Nath [19] found type of family associated with depression but age was not associated, Bineetha, Vijayakumar [20] found sex, alcohol and tobacco consumption were not associated with depression, but that being unemployed was, Manandhar, Risal [1] found sex, alcohol consumption were not associated with depression, but that having a chronic health problem and physical capability were. Similarly, other studies have found that family support, living with children, stress, a lack of decision-making, and family income are all strongly associate to depression [1,2,21].…”
Section: Discussionsupporting
confidence: 86%
“…Contextual characteristics such as family support, good communication among family members, and family decision-making roles were also associated to depression. However, sex and individual factors such as cigarette use, alcohol consumption, and the presence of chronic disease were not associated to geriatric depression, which is consistent with earlier findings; a study conducted by Shrestha, Shrestha [6] found an association between the presence of chronic disease and depression and no association between age and depression, John and Nath [19] found type of family associated with depression but age was not associated, Bineetha, Vijayakumar [20] found sex, alcohol and tobacco consumption were not associated with depression, but that being unemployed was, Manandhar, Risal [1] found sex, alcohol consumption were not associated with depression, but that having a chronic health problem and physical capability were. Similarly, other studies have found that family support, living with children, stress, a lack of decision-making, and family income are all strongly associate to depression [1,2,21].…”
Section: Discussionsupporting
confidence: 86%